2019
DOI: 10.1080/1331677x.2019.1686045
|View full text |Cite
|
Sign up to set email alerts
|

How brand equity affects firm productivity: The role of R&D and human capital

Abstract: This article provides fresh insights into the link between brand equity and firm-level productivity, including the direct effect and the potential interaction effect with research and development (R&D) and human capital. A panel data model using Chinese listed companies' accounting data from 2012 to 2017 is constructed to test our hypotheses. The main findings are as follows: First, both the direct effects and the potential interaction effects with R&D and human capital are significant. Second, a larger direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…With the help of human capital, companies can create and develop organizational structure and strategy. R&D and human resources can be used to improve the impact of brand equity on a company's profitability, although as noted by He et al (2019), the effectiveness of such use may be negligible in nonstate companies and companies in the service sector. It is noted that the quality of the SME business environment also depends on human capital -quality employees trained to work in this area (Kotaskova & Rozsa, 2018).…”
Section: Human Capital In Smes Management or Service Sectormentioning
confidence: 99%
“…With the help of human capital, companies can create and develop organizational structure and strategy. R&D and human resources can be used to improve the impact of brand equity on a company's profitability, although as noted by He et al (2019), the effectiveness of such use may be negligible in nonstate companies and companies in the service sector. It is noted that the quality of the SME business environment also depends on human capital -quality employees trained to work in this area (Kotaskova & Rozsa, 2018).…”
Section: Human Capital In Smes Management or Service Sectormentioning
confidence: 99%
“…This can also fasten the internationalization process and will enable them to compete the efficiently in global markets in terms of quality of exports and standardization. He et al [30] conducted a study using panel data model on Chinese listed companies and by taking data from 2012 to 2017. The results of their study suggest that brand equity will play a vital and important role in the future growth of China whereas proper attention should be devoted to it in terms of policy and regulation.…”
Section: The Analysis Of Chinese-style Innovation Characteristicsmentioning
confidence: 99%
“…Sumner et al (2019) note that during R&D, human capital has the key role (shown by the example of medicine). He et al (2019) show how brand's capital influences the company's efficiency and notes the main role of R&D and involved human capital. Chen et al (2019) offer a perspective model and algorithm of optimization of planning of R&D programs with limited human resources.…”
Section: Literature Reviewmentioning
confidence: 98%